The Dharma of Doctor Strange: The Shifting Representations of Tibet and Tibetan Buddhism within a Comic Book Serial. (13th August 2015) - Gruber, Joel
Abstract : In 1963, Stan Lee and Steve Ditko created a mystical comic book superhero named Doctor Strange. In the last fifty years, the character has appeared in hundreds of monthly serials, guest cameos, and graphic novels. In this article, I argue that the sequential panels of art, along with the narratives plotting Doctor Strange's adventures, provide three different (but interrelated) histories of late twentieth-/early twenty-first century America. First, they document a visual history of a distinctly American pop-fascination with the "Orient, " and with Tibet in particular. Second, over the course of a half-century the comic serial maps the Americanization of quasi-occult and quasi-Buddhist practices. Third, the transformation of Doctor Strange, as an individual with hopes, fears, and an evolving worldview, provides insight into the implied but seldom expressed religiosity of generations of Buddhist studies scholars.